Evaluation of EVALUE, SIPAR_ID and INFILT Models for Estimating of Kostiakov infiltration parameters in Furrow Irrigation - H. Ramezani Etedali; H. Ebrahimian; F. Abbasi; A. M. Liaghat (علوم و مهندسی آبیاری, 2012)
Estimation of infiltration parameters is very difficult in furrow irrigation while they have very important effect in design and evaluation of surface irrigation systems. There are different methods for estimating infiltration parametersbased on mathematical models such as EVALUE, SIPAR_ID and INFILT. EVALUE model uses direct solution whereas two other models are based on inverse solution. The objective of this study is to evaluate these models to estimate infiltration parameters in furrow irrigation. Twelve data sets of experimental blocked-ended and free draining furrows were used in this assessment. The data sets were under different conditions, e.g. length, slope, and flow regime. Using the estimated infiltration parameters, the total infiltrated volume was predicted to evaluate the accuracy of the mathematical models. The results indicated that EVALUE and SIPAR_ID provided the lowest errors for estimating the infiltrated volume with RMSE 1.86 and 1.78 m3 at blocked furrows, respectively. At free draining furrows, SIPAR_ID with RMSE 1.11 m3 has the best result. The models specifically INFILT with RMSE, 1.63 m3 provided lower accuracies in cutback flow regime relative to continuous flow.